THE ROLE OF MONKS TOWARD DEVELOPMENT OF COMMUNITY IN PHRAE CITY SOCIETY - Kaewmola, Phromares; PhrakruSoontorndhammanithat (Journal of Buddhist Education and Research (JBER), 2019)
The Most of people who live in Phrae community are respected Buddhism and it is bound sine the past to the present time. There are the Buddhist monks who is brought the Buddha teaching to teach the people in the society for having the moral and apply in the life style. The Buddhist monks is the center of mind of people in Phrae community and they have also played important role to develop community in Phrae city society until it can change to better direction. It can be made Phrae community to become pleasant society. The role of monks can see clearly in community because people in community have close up with Buddhist monks who is one part of social and religious institution. Therefore, the Buddhist monks have to show the role in community developing and community and activities’s assistance. It has led to community strength and be example of the community other on words.